Learning to Unlearn the Teaching and Assessment of Academic Writing - Poe, Mya (Discourse and Writing/Rédactologie, 2022)
The last two years have raised important questions about how we can make the teaching of academic writing more equitable. In fact, the current moment invites us to “learn to unlearn” ways of teaching academic writing that perpetuate inequity. In this reflective article, I draw on decolonial theory and antiracist theory to unwind the ways coloniality has shaped the way that I have taught scientific writing for two decades. This work begins with a discussion of the idea of learning to unlearn from decolonial theory. I then examine how that perspective can change the way we teach scientific communication—for example, in contextualizing the development of scientific knowledge as a series of epistemological developments and exchanges, rather than from a zero point of Western thought. Spiraling outward from the classroom, I reflect on how scientific writing is part of a larger matrix of institutional structures that unwittingly compound colonial legacies inequities. In the end, if we are to address inequity in the teaching and assessment of academic writing in new ways, then we need to acknowledge and challenge the legacies of coloniality in the teaching and assessment of academic writing.